2010
DOI: 10.1074/jbc.m110.168039
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 Deficiency Results in Severe Hypoglycemia by Enhancing Both Basal and Insulin-stimulated Glucose Uptake in Mice

Abstract: Glucose homeostasis in mammals is mainly regulated by insulin signaling. It was previously shown that SIRT6 mutant mice die before 4 weeks of age, displaying profound abnormalities, including low insulin, hypoglycemia, and premature aging. To investigate mechanisms underlying the pleiotropic phenotypes associated with SIRT6 deficiency, we generated mice carrying targeted disruption of SIRT6. We found that 60% of SIRT6 ؊/؊ animals had very low levels of blood glucose and died shortly after weaning. The remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
187
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(201 citation statements)
references
References 41 publications
11
187
2
1
Order By: Relevance
“…SIRT6-knockout mice have aging-like phenotype, including severe hypoglycemia and loss of subcutaneous fat, leading to death at early age (Mostoslavsky et al, 2006;Xiao et al, 2010). SIRT7-knockout mice display cardiac hypertrophy (Vakhrusheva et al, 2008), whereas SIRT2-knockdown mice develop tumorigenesis, leading to the notion that SIRT2 acts as a tumor suppressor (Park et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…SIRT6-knockout mice have aging-like phenotype, including severe hypoglycemia and loss of subcutaneous fat, leading to death at early age (Mostoslavsky et al, 2006;Xiao et al, 2010). SIRT7-knockout mice display cardiac hypertrophy (Vakhrusheva et al, 2008), whereas SIRT2-knockdown mice develop tumorigenesis, leading to the notion that SIRT2 acts as a tumor suppressor (Park et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hafner et al (2010) have identified a role for SIRT3 in cell protection and mitochondrial function in heart tissue during aged and induced stress: SIRT3 deacetylates cyclophilin D, inhibiting apoptosis by the opening of the mitochondrial permeability transition pore, while the loss of SIRT3 activity leads to increased cardiac stress and so to a decline in cardiac function. SIRT3 has been shown to block cardiac hypertrophy by reducing ROS synthesis from the mitochondria (Kim et al 2010). A recent study of Porter et al (2014) showed that under ischemic/reperfusion insult, at heart level, SIRT3 +/− adult and wild-type aged mice showed a similar phenotype of injury, resulting in a significant myocardial infarction area with respect to wild-type adult hearts.…”
Section: The Sirtuin Familymentioning
confidence: 97%
“…In particular, SIRT6-deficient mice are smaller compared to the wild-type mice and, remarkably, show a premature aging-like phenotype that includes cardiac hypertrophy and heart failure, lymphopenia, reduced subcutaneous fat, lordokyphosis, genomic instability, hypoglycemia, low blood insulin-like growth factor (IGF) level, increased glucose uptake, and fatty liver (Kim et al 2010;Schwer et al 2010;Xiao et al 2010). As result, SIRT6-deficient mice die around 4 weeks after birth Pillai et al 2014).…”
Section: The Sirtuin Familymentioning
confidence: 99%
See 2 more Smart Citations